Sistema de protección al consumidor en el marco de un modelo dinámico de gobernanza. (2018)
The right of consumers develops constitutional principles that allow the integration of a structured co-government model based on agents that cooperate for the functioning of the consumer protection system in Colombia. The role played by each of the agents determines the greater or lesser protection in consumer relations. The qualitative analysis of the different levels of functioning of the system related to the sociopolitical interactions between the public control authorities, organized civil society, suppliers of goods and services in market relations and the existence of a sanctioning authority, determines the greater or less protection of consumer rights. The fissures in protection derive from a soft interaction in the operating levels of co-government, which negatively affect the development of consumer relations.